Phylogenetic diversification and developmental implications of poly-(R)-3-hydroxyalkanoate gene cluster assembly in prokaryotes. Issue 13 (26th June 2017) - Kutralam-Muniasamy, Gurusamy; Corona-Hernandez, Juan; Narayanasamy, Ravi-Kumar; Marsch, Rodolfo; Pérez-Guevara, Fermín
Abstract: Many polyhydroxyalkanoates (PHAs) system genes, such as phaC, phaA, phaB, phaR, phaP and phaZ, are often found to be organised in the form of operon-like clusters. In this study, a genome survey was performed to identify such clustered PHA systems among 256 prokaryotic organisms. These data were then used to generate a comprehensive 16S rRNA species tree depicting the phylogenetic distribution of the observed clusters with diverse gene arrangements. In addition, the gene occurrences and physical linkages between PHA system genes were quantitatively estimated. From this, we identified a centrally connected hub gene, i.e. the phaC gene of PHA. Furthermore, a comparative investigation was performed between the clusters of PHA and glycogen, which decoded the role of the hub gene in the cluster organisation of both systems. Together, these findings suggest that the highly connected hub gene might contribute substantively towards the organisation and maintenance of the gene network connectivity in the clusters, particularly in the storage reserve systems. Abstract : This paper presents the phylogeny of PHA gene clusters in prokaryotes.